Estilos de liderança e sua relação com comprometimento e clima organizacional - estudo de caso em um hospital público e de ensino - Feitosa, Raquel Libório (2008)
This study aims to analyze the relationship between leadership and commitment styles and the organizational climate in a public training hospital in the State of Ceará. A turning point that directed the research to this type of hospital was the scope and importance of acts performed by such organizations. They carry on practice-theory teaching to a wide extent and develop social welfare by offering a great deal of health assistance. Other important and equally decisive issues in the research were the following aspects in such organizations: the decision-makers are in the highest ranks and either the infrastructure is precarious or resources are often scarce at work. Work psychodynamics and French psychosociology were the theoretical references employed. The qualitative approach was used in the research on leadership styles. Analysis of data and their respective interrelationship was supported by another comprehensive study previously produced during a quantitative-qualitative research on organizational climate and commitment at the same hospital.